2023
DOI: 10.3389/fmicb.2023.1147187
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community composition and metabolic potential during a succession of algal blooms from Skeletonema sp. to Phaeocystis sp.

Abstract: Elucidating the interactions between algal and microbial communities is essential for understanding the dynamic mechanisms regulating algal blooms in the marine environment. Shifts in bacterial communities when a single species dominates algal blooms have been extensively investigated. However, bacterioplankton community dynamics during bloom succession when one algal species shift to another is still poorly understood. In this study, we used metagenomic analysis to investigate the bacterial community composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Most eukaryotic phytoplankton are VB-deficient types, as they require exogenous B vitamins for growth maintenance [65]. A previous study showed that Rhodobacteraceae dominate in diatom bloom caused by Skeletonema [66]. Based on functional gene inference in the study, Rhodobacteraceae may be involved in the synthesis of vitamin B 1 and B 2 for the host.…”
Section: Correlations Of Different Prokaryotes With Species Responsib...mentioning
confidence: 84%
“…Most eukaryotic phytoplankton are VB-deficient types, as they require exogenous B vitamins for growth maintenance [65]. A previous study showed that Rhodobacteraceae dominate in diatom bloom caused by Skeletonema [66]. Based on functional gene inference in the study, Rhodobacteraceae may be involved in the synthesis of vitamin B 1 and B 2 for the host.…”
Section: Correlations Of Different Prokaryotes With Species Responsib...mentioning
confidence: 84%
“…is accompanied by the microbiota changes from the dominant Alphaproteobacteria to Bacteroidia and Gammaproteobacteria as well as from the Rhodobacteraceae to Flavobacteriaceae accordingly. [ 56 ] Alterations in the metabolism of sulfur, porphyrin, tryptophan, biotin, and quorum‐sensing signals were seen in the bacteria that corresponded to the predominant species of algae. [ 56 ] It would be interesting to look into whether comparable changes in dominant algae species and corresponding bacteria can be modeled in vitro, as no functional investigations were reported.…”
Section: Microalgae‐bacteria Interactions Increase Production Efficiencymentioning
confidence: 99%
“…[ 56 ] Alterations in the metabolism of sulfur, porphyrin, tryptophan, biotin, and quorum‐sensing signals were seen in the bacteria that corresponded to the predominant species of algae. [ 56 ] It would be interesting to look into whether comparable changes in dominant algae species and corresponding bacteria can be modeled in vitro, as no functional investigations were reported.…”
Section: Microalgae‐bacteria Interactions Increase Production Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…While this relationship benefits the bacteria, it can also benefit the algal cell via a mutualistic relationship (Kazamia et al, 2012;Zhou et al, 2016;Mugnai et al, 2023). Many algae require vitamin B12 to function properly, which is provided by bacteria in the phycosphere (Fuentes et al, 2016;Yao et al, 2019); different bacteria can provide a variety of vitamins including B1 and B7 (Lutzu and Turgut Dunford, 2018;Zhu et al, 2023). Bacteria present in the phycosphere can contribute to algal defense by releasing compounds that impede invasive species, such as the production of antibiotics and toxins (Kizhakkekalam and Chakraborty, 2020).…”
Section: The Phycospherementioning
confidence: 99%